The Effectiveness of Education on Mothers' Anxiety Levels in Facing Menopause - Purnama Sari, Kurnia Indriyanti; Kiftiyah, Kiftiyah (Universitas Islam Lamongan, 2022)
Â Elderly is someone who has reached the age of 60 (sixty) years and over. The world's elderly population (age 60 years and over) is growing very fast, even the fastest when compared to other age groups. Menopause is a condition in a woman who experiences a decrease in ovarian function which results in a decrease in the production of the hormone estrogen. This situation, among other things, will result in the cessation of menstruation forever. The purpose of this study was to determine the effectiveness of education on the level of maternal anxiety in facing menopause. The design of this study is analytic with this is a pre-experiment with the One Group Pre-post Test design. By using a cohort approach. Population using total sampling. The population in this study were all mothers who lived in the Cempokolimo elderly hut, Pacet District, Mojokerto Regency. A sample of 31 respondents was obtained in November 2022. Data was collected by means of a questionnaire using the HARS scale with 14 questions and modified according to the emergence of changes, signs and symptoms that can cause anxiety in menopausal women. The statistical test used was the Wilcoxon signed rank test. The results showed that most of the anxiety levels before being given education (pre test) were mild anxiety, namely 18 people (58.1%), not anxious 3 people (9.7%), moderate anxiety 8 people (25.8 %) and severe anxiety in 2 people (6.4%). Results Most of the anxiety levels after being given education (post test) were not anxious, namely 18 people (58.1%), mild anxiety 10 people (32.2%) and moderate anxiety 3 people (9.7%) ). Statistical Test Results Based on the results of the Wilcoxon Signed Rank Test it shows that the significance value is 0.000 <Î± (0.05). Because the significance value is < Î± (0.05), then H0 is rejected, which means that there is an influence on the effectiveness of education on the level of anxiety of mothers in facing menopause. the changes that are going through. Seeing the results of this study, there is still a need for regular health education education to reduce mothers' anxiety in dealing with menopausal changes